Strains induced around cutoff walls of earth dam under full reservoir and drawdown conditions - S.S. Athani; C.H. Solanki; B.G. Mohapatra; G.R. Dodagoudar (International Association of Lowland Technology, 2017)
This paper presents the study pertaining to the strains that are developed near the cutoff walls employed in the foundation medium of the dam section. A total of sixteen finite element simulations are considered in the study, where the combination and placement of the cutoff walls in the foundation medium are varied. A cutoff wall is made to act as a seepage barrier with assigned linear elastic properties. A hypothetical earth dam of height 35 m is provided with a slope of 1V: 2.5H for both the downstream and the upstream sides. The finite element analyses are carried out using PLAXIS – 3D to obtain the principal strains and their variation with respect to time for two different conditions viz. Full reservoir steady seepage and Drawdown conditions. The variations in strains in the dam section and in the foundation medium are found to be more predominant for the two barriers with increased Young’s modulus having a spacing of 15 m, first one being located at 0 m and second at 15 m from the center of the dam. The excessive strains would initiate cracks in the cutoff walls. This fact has to be taken to advantage while finalizing the sections for the cutoff walls.